7 years of Ugnayan ng Pahinungod System the gurong pahinungod program in focus. (Ugnayan ng Pahinungod System, 2001)
"As the Pahinungod System Office comes to a close on March 31, 2001, we leave the pahinungods - past, present and future - this token of thanksgiving. Likewise, it poses the continuing challenge to the University of the Philippines to harness its comparative advantage in education in the service of the nation."--Preface.